Countering Islamophobia through Civilizational Narratives: Global Media, Muslim Intellectuals, and the Memory of Islamic History - Muhammad Abdurrayid, R.Irfan (Sekolah Tinggi Agama Islam Kuningan, 2025)
Background: Islamophobia has become one of the most persistent forms of hatred globally, operating through racial, religious, spatial, and digital dimensions that shape negative narratives about Islam and Muslims via global media.Objective: This study analyzes how global media construct civilizational narratives contributing to Islamophobia and examines counter-narratives developed by Muslim intellectuals who mobilize Islamic historical memory.Method: Using qualitative multi-case study design combining critical discourse analysis of 60-80 global media texts and narrative analysis through in-depth interviews with 20-25 Muslim intellectuals from Global North and South contexts.Findings and Implications: Media systematically construct Islam as a civilizational threat through conflict frames (72%) and terrorism associations (64%), while Muslim intellectuals counter this through historical reclamation of Islamic Golden Age contributions, theological articulation, spatial justice advocacy, and digital resistance strategies.Conclusion: The study proposes a 'Civilizational Counter-Narratives' model integrating multiple Islamophobia dimensions, offering a theoretical framework for understanding Islamophobia as narrative contestation and practical strategies for Muslim communities and policymakers globally.